Consuming Passions: Child Abuse, Fetishism, and "The New World Order" - Comaroff, Jean (Culture, 1997)
While our current world — post-colonial, late-capitalist, translocal — might seem uniquely plagued by eroding frontiers and virtual realities, it is still peopled by beings who try to build shelters on what they take as relatively firm cultural ground. This paper explores one African instance of how people live at the juncture of global currents, how they deal with the "beat" of heteroglossia. I focus on the changing figure of the "post-colonial" witch — the witch who trades in commodities and travels by taxi — and I explore his/her characteristic obsessions. How do such figures bespeak late twentieth-century conditions? Why are they increasingly preoccupied with the bodies of the young? Does this bear any relation to what underlies the rising terror, in many Western contexts, of the physical vulnerability of children?